GUIDING QUESTIONS TECHNIQUE TO IMPROVE STUDENTS’ WRITING SKILLS: RECOUNT TEXT - Muhtar, Siti Nuraeni; Rustina, Lina Rustina; Dalimunthe, R Nadia R P (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2020)
This research aimed to find out whether there was an improvement of the students’ skills in writing recount text after using guiding questions as a technique of writing. The method applied in this research was a quantitative method which use one group pre-test and post-test design. Random group sampling is used as the technique in taking a sample. Afterthat, the researcher took one class consist of 31 of second grade students as research participants. This research was held in 6 meetings involved pre-test, four meetings for treatment, and post-test. The instrument of data collecting was a written test. In analyzing the data, the researcher used SPSS v.16 and t-test.